Internal mammary lymph nodal response to neoadjuvant chemotherapy on imaging and breast cancer prognosis. (December 2022) - Adam, Richard; Duong, Tim Q; Hodges, Laura; Lu, Jinyu; Maldjian, Takouhie
Abstract: Background: Pathologic complete response (pCR) to neoadjuvant chemotherapy (NAC) is an important prognostic indicator in breast cancer. Internal mammary lymph node involvement is not currently included in pCR determination, as sampling at the time of surgery is not routinely performed. Methods: Pre and post neoadjuvant chemotherapy MRI or PET/CT imaging response of the internal mammary lymph node chain was utilized as a surrogate to pCR and imaging data was correlated with patient outcomes. Results: Internal mammary lymph node response to NAC was associated with disease free survival over the course of this study, regardless of whether axillary nodal pCR was achieved. Conclusion: Internal mammary lymph nodal response to NAC is an important prognostic indicator. Potential use of internal mammary lymph node resolution as an imaging data input for AI models that predict pCR post-NAC may improve accuracy and other metrics in pCR prediction. Highlights: IMLN involvement is an important prognostic factor in breast cancer, yet not included in pCR, as not routinely sampled. We report imaging response of internal mammary lymph node basin (IMLN) and correlate this with patient outcomes. IMLN imaging data may potentially be used as a surrogate for IMLN pCR and as an input for AI models to predict post NAC pCR. .